Peran Gapoktan Muji Makmur dalam Memberdayakan Kelompok Tani melalui Produksi Pupuk Alternatif di Desa Bronjong Kecamatan Bluluk Kabupaten Lamongan - Maharani, Zahra Sukma; Nusantara, Widya (J+PLUS UNESA, 2024)
This research aims to describe the implementation stages and the driving and inhibiting factors for empowerment through alternative fertilizer production carried out by Gapoktan in empowering farmer groups. This type of research is descriptive research using a qualitative approach. The subjects of this research were facilitators, Gapoktan members and farmer groups. Data collection techniques were carried out using interview techniques, participant observation and documentation. Data analysis was carried out using 4 steps, namely data collection, data reduction, data presentation, and drawing conclusions. Data validity is carried out with credibility, dependability, confirmability and transferability. Source triangulation and member checking are techniques used to check credibility in this research.The results of this research show that the role of Gapoktan Muji Makmur in empowering farmer groups through the production of alternative fertilizers in this implementation stage increases the independence of the residents of Bronjong Village which is influenced by the driving and supporting factors for empowerment.